Dynamic capabilities in times of educational change : the viewpoint of school leadership - Johara, Kazi (2018)
Nowadays educational organizations experience rapid changes, due to globalization, technological advancement, changing knowledge and competencies, and increasing social, political and cultural complexity. Consequently, these issues pose capability challenges to their leadership. In the rapidly changing educational circumstances, educational leadership needs to develop dynamic capabilities by integrating and reconfiguring their internal and external resources and competencies. However, few research have been carried out to comprehend the development of dynamic capabilities in educational organizations. Therefore, the aim of this study was to explore how educational organizations develop dynamic capabilities in times of educational change to meet capability challenges in rapidly changing circumstances. The qualitative case study took place in Finland and focused on participants that hold different kinds of leadership positions in Finnish comprehensive schools. Convenience sampling was used to select participants for the study, and an open-ended questionnaire, with five open-ended questions, was developed to explore school leadership’s viewpoints on developing dynamic capabilities in their schools in order to deal with the rapid educational change. Qualitative content analysis was used to analyze the data. The results of the study showed that the particular Finnish school leadership experienced capability challenges in reappraising resources, integrating technologies into instruction, reconfiguring teaching and learning practices, and, more importantly, motivating teachers to take part in the changing process. This study also found that the school leadership tried to develop dynamic capabilities by reconfiguring their existing resources and competencies to cope with these capability challenges.